2015
DOI: 10.1007/s00592-015-0782-4
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges of HOMA-IR in normal-weight and obese young Caucasians

Abstract: Percentiles of HOMA-IR varied significantly in young Caucasians depending on sex, age, and BMI category. The 75th percentile may represent an accurate cutoff point to suspect the occurrence of one or more CMRFs among high total cholesterol and triglycerides, low HDL cholesterol, and ALT ≥ 40 UI/l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(175 citation statements)
references
References 32 publications
11
152
1
11
Order By: Relevance
“…[8][9][10][11][12][13]26,32 In this study, indices showed differences in insulin sensitivity with puberty development similar to baseline insulin. Schwartz et al found a modest correlation between insulin sensitivity surrogates 33 Only insulin level and the HOMA-IR index showed changes in insulin sensitivity during prepuberty.…”
Section: Discussionsupporting
confidence: 50%
“…[8][9][10][11][12][13]26,32 In this study, indices showed differences in insulin sensitivity with puberty development similar to baseline insulin. Schwartz et al found a modest correlation between insulin sensitivity surrogates 33 Only insulin level and the HOMA-IR index showed changes in insulin sensitivity during prepuberty.…”
Section: Discussionsupporting
confidence: 50%
“…21,22 HOMA-IR was calculated by multiplying glucose (mg/dL) by insulin (µU/mL) and dividing by 405. 23 The cutoff value of 2.56 was used to diagnose for IR, as previously reported in Korean adults.…”
Section: Definition Of Irmentioning
confidence: 99%
“…In order to account for changes in HOMA-IR values that occur with age and sex, HOMA-IR values were converted to Z-scores, derived from HOMA-IR percentiles from an overweight/obese population sample. 29 Because reference values were only available up to the 97th percentile, in cases where the HOMA-IR exceeded the 97th percentile, we simply assigned the Z-score corresponding to the 97th percentile (ie, 1.88).…”
Section: Measurementsmentioning
confidence: 99%
“…A strength of our study is evaluation from the time of SDB diagnosis and intervention with PAP therapy. Further, we have used HOMA-IR percentiles, which are standardized by age and sex, 29 which partially account for pubertal status in the evaluation of metabolic status.…”
Section: Metabolic Markersmentioning
confidence: 99%